State Minimum Wage Increases As a Potential Policy Lever to Reduce Black?White Disparities in Hypertension (Mary Ann Liebert, 2023)
Introduction: Black adults are disproportionately burdened by hypertension. Income inequality is associated with elevated risk of hypertension. Minimum wage increases have been explored as a potential policy lever to address the disparate impact of hypertension on this population. However, these increases may have no significant impact on health among Black adults due to structural racism and ?diminished gain? of health effects from socioeconomic resources. This study assesses the relationship between state minimum wage increases and Black?White disparities in hypertension. Methods: We merged state-level minimum wage data with survey data from the Behavioral Risk Factor Surveillance System (2001?2019). Odd survey years included questions about hypertension. Separate difference-in-difference models estimated the odds of hypertension among Black and White adults in states with and without minimum wage increases. Difference-in-difference-in-difference models estimated the impact of minimum wage increases on hypertension among Black adults relative to White adults. Results: As state wage limits increase, the odds of hypertension significantly decreased among Black adults overall. This relationship is largely driven by the impact of these policies on Black women. However, the Black?White disparity in hypertension worsened as state minimum wage limits increased, and the magnitude of this disparity was larger among women. Conclusion: States having a minimum wage above the federal wage limit are not sufficient to combat structural racism and reduce the disparities in hypertension among Black adults. Rather, future research should explore livable wages as a policy lever to reduce disparities in hypertension among Black adults.